Impact of electrification on the welfare of rural households in Ethiopia - Mekonnen, Dawit; Arega, Tiruwork; Yiman, Seid; Ringler, Claudia (2022)
Dawit Mekonnen, Tiruwork Arega, Seid Yimam, and Claudia Ringler